Comparative Study on Job Security and Stability among German and Spanish Workers and Their Ability to Work from Home - Huth, Andreas (Naše gospodarstvo/Our economy, 2025)
This research article analyses the situation in the labour markets in Germany and Spain using a comparative study to identify differences in job security and stability and the possibility of working from home. The study is based on data from statistical sources provided by Eurofound (2024) with a sample of 907 employees in Germany and Spain. A binary logistic regression was performed, where the dependent variable was the binary variable country (Germany and Spain) and the independent variables are related to job security and stability (job loss, employment opportunities, recognition, performance expectations, employment contract). In addition, a Chi-square independence test was performed to determine the difference between countries regarding working conditions and teleworking. The analysis in this study reveals a clear difference between the labour markets in Spain and Germany. German workers are in a significantly more favourable position than Spanish workers. For this reason, Germany must continue to improve the quality of its labour market to ensure the sustainability of employment.